Leadership in Action a Question of Leadership - How Much of Themselves Should Leaders Bring to their Work? - Hoppe, Michael H. (Center for Creative Leadership, 2004)
When leaders are aware of and reconcile their multiple social identities and help those they lead do the same, organizations have a better chance of reaching maximum potential in their missions, visions, cultures, and strategic objectives.
Title from content provider
Keywords: Leadership